Length-weight relationship and condition factor of West African Lungfish (Protopterus annectens) in Kware Lake, Sokoto State, Nigeria - Argungu, L.A.; Jibrin, H.; Mohammed, A.; Abdullahi, S.; Muhammad, U. (ADAN JOURNAL OF AGRICULTURE, 2026)
This study examined the length–weight relationship (LWR) and condition factor (K) of West African lungfish, Protopterus annectens from Kware Lake, Sokoto State, Nigeria, to assess its growth pattern, health status, and environmental adaptation. A total of 77 specimens were collected and analysed using standard morphometric methods. The relationship between length and weight was expressed by the equation W = aLᵇ, with the logarithmic transformation used to determine regression parameters. Results showed that Protopterus annectens exhibited a negative allometric growth pattern across sexes, with regression coefficients (b) of 0.41 for males, 0.56 for females, and 0.39 for combined sexes all less than 3, indicating that the fish grows faster in length than in weight. The coefficient of determination (R²) ranged from 0.69 to 0.76, revealing a strong positive correlation between length and weight. The mean total length and body weight were 32.70 ± 1.42 cm and 100.90 ± 6.99 g, respectively. The mean condition factor values were 0.41 (male), 0.34 (female), and 0.37 (combined sex), suggesting that Protopterus annectens populations in Kware Lake are in moderate physiological condition. The observed growth pattern and condition factors may be attributed to environmental factors, food availability, and anthropogenic influences within Kware Lake. The study concludes that Protopterus annectens in Kware Lake maintains a relatively stable population structure and ecological balance despite exhibiting negative allometric growth. It recommends the implementation of sustainable fisheries management practices, regular monitoring of water quality, and control of anthropogenic activities to maintain ecosystem integrity and ensure long-term fish productivit